2008
DOI: 10.1177/1466424007085224
|View full text |Cite
|
Sign up to set email alerts
|

Lessons to be learned — Langerhans' cell histiocytosis

Abstract: Langerhans' cell histiocytosis (LCH) is a neoplastic disease due to uncontrolled proliferation of Langerhans' cells (LCs); damage to organs involved appears to be due to the various cytokines secreted. The true cause of LCH remains a mystery. LCH can present at any age; there is female predominance and the skin is often the first site to be involved. Scaly papules, vesicles, purpuric nodules, plaques and ulcers are the main diverse presentations typically found on the scalp, flexures (including the perineum), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Plasschaert et al 15 found that adults with EG have a higher chance of recurrence compared with children. Nevertheless, as the course of the disease can be unpredictable at times, the potential for unifocal disease to become multifocal should not be underestimated and therefore long term follow-up is mandatory 16. Monoclonal antibodies directed against CD1a or CD207 may evolve as one of the potential treatment modalities in the future 17…”
Section: Discussionmentioning
confidence: 99%
“…Plasschaert et al 15 found that adults with EG have a higher chance of recurrence compared with children. Nevertheless, as the course of the disease can be unpredictable at times, the potential for unifocal disease to become multifocal should not be underestimated and therefore long term follow-up is mandatory 16. Monoclonal antibodies directed against CD1a or CD207 may evolve as one of the potential treatment modalities in the future 17…”
Section: Discussionmentioning
confidence: 99%
“…The scalp accounts for 4% to 6.9% of cutaneous metastasis. Causes of scalp skin metastasis are commonly seen with breast cancer, melanoma, angiosarcoma, and renal, lung, and gastrointestinal malignancies . Angiosarcoma is a rare aggressive malignant tumor of vascular endothelial cells, the face and scalp regions account for more than 50% of cutaneous angiosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestation varies widely due to the differences among age of onset, the proliferation rate of Langerhans cells and the involved tissues and organs [ 8 ]. The research by Braier et al [ 9 ] indicated that the incidence rate of rashes in LCH was about 24%.…”
Section: Discussionmentioning
confidence: 99%